Contributions to the Technical Training of Handball Players Specialized in the Wing Post - Bernicu , Andrei RÄƒzvan; Ion, MihÄƒilÄƒ; Nicolae, MihÄƒilescu (Arena-Journal of Physical Activities, 2021)
Aim: The level of performance achieved at the current stage, both internationally and internally, is very high and can only be achieved by players whose performance capability is particularly high and steadily increasing. The field of game technology has expanded a lot. Increasing the spectacularity of this game, coupled with its spread across the continents, has had repercussions on the organization of handball at junior level. New methods have emerged, which performance players perform with high craftsmanship, doubled by special physical qualities. Methodology : the experiment took place between September 2016- Juin 2017, in the city of Suceava, with 3 players specialized on the wing position from the under 18 team Suceava Sports High School. During this period the team maintained its regular training program, the wings following our proposed program to analyze its effect on improving the tracking parameters. We estimate that using efficient means of action and adapting them to the post of the wing player will increase the performance of the game and individual value to handball players specializing in the wing. Results: the mean results recorded at the technical level, show good differences between initial test (IT) and final test (FT): - dribling among the rounds: IT= 6,21Â±0,009 sec., and FT= 5,80Â±0,02 sec.; - passing in two out of the way: IT= 5,16Â±0,005 sec., and FT= 4,80Â±0,01 sec.; - triangle shift, gate throw: IT= 12,48Â±0,01 and FT= 12,0Â±0,01, show a breakthrough in all the sustained samples and the statistical analysis demonstrates a homogeneity of the research group. Given the importance of the â€œwingâ€ role in organizing and directing the field play in this paper, I presented the tasks in the post, determined by the action areas and the contribution in the attack phases. Conclusions: we can assert that the hypothesis from which I left is confirmed and the purposes of the work have been achieved. I think the study has achieved its goal by showing: optimization of the training, due to the selected means of action, the fulfillment of the tasks of the wings in the post, resulting from the registration of the actions in the attack, as well as the efficiency in their areas of action, as revealed by the research.